The effect of autologous serum obtained after fracture on the proliferation andosteogenic differentiation of mesenchymal stem cells - Pountos, I.; Georgouli, T.; Giannoudis, P. V. (Cellular and Molecular Biology, 2008)
The purpose of this study was to investigate the potential of Mesenchymal Stem Cells (MSCs) obtained from patients suffering from fractures to proliferate and differentiate towards osteogenic lineage with the use of autologous serum. In addition the effect of medium supplementation with the use of autologous serum obtained at different time points (patients' admission, first, third and seventh post-operative day) was investigated. In total eight patients suffering from lower limb long bone fractures with mean age of 39 (range 22- 68 years) were included in this study. MSCs were isolated and cultivated in 10% of either Fetal Calf Serum (FCS) or autologous serum. Cellular proliferation was examined by XTT assay and Vybrant assay. The osteogenic differentiation was assessed by total calcium production and alkaline phosphatase production. Cellular proliferation and osteogenic differentiation was significantly statistically higher in patients' serum obtained on admission than in FCS. A negative effect on proliferation was noted with serum obtained on the first postoperative day. Subsequently, both proliferation and differentiation were gradually increased with autologous serum collected during the 3rd and 7th postoperatively days. Autologous serum obtained after fracture is superior in terms of proliferation and osteogenic differentiation to the currently used FCS. Surgery seems to have a negative effect on the quality of serum. These findings should be considered in cases where ex-vivo expansion of MSCs is needed. Recuperation of serum's quality takes place at a later time point within the first weeks after fracture.